Fabrication of large size and high relative density tungsten tube - WANG Guang-da; LI Qiang; Dong Jian-ying; XIONG Ning; LIU Guo-hui (Fenmo yejin jishu)
The tungsten tube products with the large size and high relative density have the important application in the quartz smelting industry. To overcome the problems of cracking and low relative density in the preparation process of the large size tungsten tube, the mixing experiments of tungsten powders with the different particle sizes were carried out, and the effect of mixing time on the compaction strength was studied. It is found that the particle size distribution can be effectively reduced and the particle uniformity can be improved by the further air crushing treatment for the mixed tungsten powders. When the pressing pressure is more than 230 MPa, the compaction strength will not be improved by prolonging the holding time or increasing the pressing pressure.The temperature for the tungsten tube with the higher shrinkage rate concentrates below 1600 ℃ in the sintering experiment by slow temperature rising. Therefore, the relative density of the tungsten tube can be improved by prolonging the sintering time at medium and low temperature.